2021
DOI: 10.3390/biomedicines9060584
|View full text |Cite
|
Sign up to set email alerts
|

Natural Photosensitizers in Antimicrobial Photodynamic Therapy

Abstract: Health problems and reduced treatment effectiveness due to antimicrobial resistance have become important global problems and are important factors that negatively affect life expectancy. Antimicrobial photodynamic therapy (APDT) is constantly evolving and can minimize this antimicrobial resistance problem. Reactive oxygen species produced when nontoxic photosensitizers are exposed to light are the main functional components of APDT responsible for microbial destruction; therefore, APDT has a broad spectrum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(97 citation statements)
references
References 189 publications
(276 reference statements)
1
92
0
4
Order By: Relevance
“…PDT was approved in several countries for treating cancer after its approval for recurrent bladder cancer treatment by the Canadian Health Protection Branch [ 1 ]. PDT depends on the interaction of a photosensitizer (PS), delivered to target tissues, and with the light of a specific wavelength in the presence of molecular oxygen dissolved in the cytoplasm [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Upon light absorption, the PS molecules are transferred from the ground state to an excited singlet state and then to a triplet excited state via the intersystem crossing.…”
Section: Photodynamic Therapy In Treating Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…PDT was approved in several countries for treating cancer after its approval for recurrent bladder cancer treatment by the Canadian Health Protection Branch [ 1 ]. PDT depends on the interaction of a photosensitizer (PS), delivered to target tissues, and with the light of a specific wavelength in the presence of molecular oxygen dissolved in the cytoplasm [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Upon light absorption, the PS molecules are transferred from the ground state to an excited singlet state and then to a triplet excited state via the intersystem crossing.…”
Section: Photodynamic Therapy In Treating Cancermentioning
confidence: 99%
“…Two classes of PSs exist: Porphyrin PSs (three generations) and non-porphyrin PSs [ 27 ]. First-generation PSs (such as hematoporphyrins) have been developed and undergone clinical trials for more than 40 years [ 16 ]. However, they suffered various drawbacks, including (i) poor tissue penetration, (ii) low chemical stability, (iii) activation when irradiated with wavelengths below 650 nm, (iv) causing skin hypersensitivity reactions, and (v) low elimination rates and long half-lives.…”
Section: Photodynamic Therapy In Treating Cancermentioning
confidence: 99%
“…The absorption spectrum range for curcumin is between 300 and 500 nm with a maximum absorption at 435 nm. Many scientific articles indicate that curcumin can be used as a photosensitizer in photodynamic therapy, both against cancer and bacterial cells [ 32 , 33 , 34 ]. In our study, we observed the viability of MDA-MB-231 cells treated with curcumin and compound 5 in concentrations of 25 ”M using a real-time fluorescence microscope.…”
Section: Resultsmentioning
confidence: 99%
“…The perfect PS should accumulate, especially in unhealthy cells, and when light is applied, it should produce toxic species that will destroy the target tissue. Characteristics of an ideal PS are the following: high absorption with maximum absorption coefficient in longer wavelengths, close to the red/infrared spectrum with deeper penetration, to make it possible to deal with grand tumors; better adhesion and fixation in unhealthy tissues than in normal ones; reliable and easy dissoluble in biological systems, permitting intravenous management and fast elimination from the organism after PDT, without residual sensitivity of the skin to light or long-term photosensitization; very good chemical balance and insignificant toxic effect on cells in the absence of light or in low darkness; long triplet lifespan and high triplet state effect, as well as high efficiency for triplet formation and singlet oxygen generation; reduced photobleaching and genuine fluorescence, low production price [6,[23][24][25][26].…”
Section: Photosensitizers and Photodynamic Therapymentioning
confidence: 99%